Correlation of electric conductivity values with the dairy milk quality - Nova Dilla Yanthi; Syahruddin Said; Anneke Anggraeni; Retno Damayanti; Muladno . (Indonesian Center for Animal Research and Development (ICARD), 2018)
Milk, as the prime source of food for mammals, has an electrolyte to replace the loss of body fluid caused by activity or metabolism process. The total electrolyte concentration can be measured based on conductivity value from the nutritional content. Therefore, the parameter of the quality of milk with conductivity value can be a benchmark for quality and selling value of milk, making it simpler to be implemented in the field. The aim of this research is to analyze the relation between electric conductivity (EC) with the content value of cow milk. The milk was taken from 10-30 cows from a farm in Lembang (district of West Bandung), Pengalengan (district of Bandung), Tasikmalaya, Sumedang, Subang, Sukabumi and Bogor of West Java Province. The milk was put in 50 ml of sterile falcon. The Probe EC count-meter CT-3031 was used to measure EC while the quality of milk was measured by Probe MilkoScanTMFT 120 (Foss). The milk quality is reflected by protein content, Fat, Total Solid (TS), Solid Non-fat (SNF), Lactose, Density, Acidity and Freeze Point Deviation (FPD). The results of this study show that the EC value in the milk gives a very real positive effect (p=<0.01) to Total Solid (TS), Solid Non-fat (SNF), Lactose, and Freeze Point Deviation (FPD). The value of EC also significantly affect (p=<0.05) the value of density in milk. Therefore, the value of EC can be used to predict the quality value of milk.